4 - Ujamaa, Ubuntu and Reimagining Pan-Africanism - Shivji, Issa G. (CODESRIA Bulletin, 2025)
Keynote Address at the International Conference on Ujamaa, Ubuntu and New Pan Africanisms, Arusha, 23-25 May 2024